Molecular detection of Mycoplasma suis in captive white-lipped peccaries (Tayassu pecari) and wild boars (Sus scrofa) in Brazil - Dias, Guilherme Bim [UNESP]; do Amaral, Renan Bressianini [UNESP]; Gatto, Igor Renan Honorato [UNESP]; Lapera, Ivan Moura [UNESP]; de Oliveira, Luís Guilherme [UNESP]; Lux Hoppe, Estevam G. [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2019)
Mycoplasma suis, the etiological agent of swine hemoplasmosis, is an epicellular bacterium that adheres to the surface of pig erythrocytes leading to deformations of the target cells. Little is known about the occurrence of M. suis in wild swine populations around the world, its economic impact on swine herds, and the risk of human infection. The aim of this study was to investigate, by quantitative real-time PCR (qPCR) based on the 16S rRNA gene, the occurrence of M. suis in a captive population of white-lipped peccaries (100 Tayassu pecari) and in free-living wild boars (14 Sus scrofa) in Brazil. None of the white-lipped peccaries were positive for M. suis, whereas seven (50%) wild boars were positive in qPCR assays. The quantification of M. suis-16S rRNA copies/μL ranged from 1.42 × 10° to 3.906 × 10 1 in positive animals, indicating a low bacteremia and a chronic carrier status in free-living wild boars. In conclusion, M. suis might be a non-frequent pathogen in wild suids maintained in captivity. Despite the low bacteremia, the prevalence of M. suis in wild boar population in Brazil seems to be high.
Keywords: Brazil; Invasive species; Mycoplasma suis; qPCR; White-lipped peccary; Wild boar